Android-Based Online Exam Information System In SMK Pertiwi Batam: Sistem Informasi Ujian Online Berbasis Android Di Smk Pertiwi Batam - Eisyaniah Desvazulinda; John Friadi; Fendi Hidayat (Journal of Vocational Education and Information Technology (JVEIT), 2021)
Batam Pertiwi Vocational School is the first vocational school in Nongsa sub-district, this school has majoring in TKJ (Computer Network Engineering), Accounting and Nursing, the problems that exist in Batam Pertiwi Batam are implementation that is still manual and value processing takes a long time and costs Great for printing questions and answer sheets. Making an android-based online exam system in the form of an application to facilitate teachers and students in the implementation of the exam. The application is designed using the Mysql database, the interface design uses Android Studio and this application is installed using an android smartphone. After the online exam application, students and teachers are easier to carry out online examinations so it does not take a long time and incur huge costs and realizes SMK Pertiwi Batam as a modern and digital-based vocational school of industrial era 4.0.